Development of Healthier Cookie Product by Utilizing Different Formulations of Durian Seed Flour - Insani, Rayyane Mazaya Syifa; Dhama, Adrian (Indonesian Journal of Life Sciences, 2020)
The increasing fast food production led to decreased consumption of dietary fiber food and increased risk of obesity and cardiovascular disease. Hence, this study aimed to utilize durian seed flour in making a healthy cookie product and observe the effect of different durian seed flour formulation (0%, 25%, 50%) to the organoleptic properties of the cookies. The cookies were analysed through sensory analysis and further statistical analysis. The addition of different formulations of durian seed flour did not significantly affect the aroma, taste, aftertaste, and overall liking of the cookies, however, it did significantly affect the texture of the cookies. The formulated cookies made with the addition of durian seed flour had better overall organoleptic attributes especially in the texture attribute. Nevertheless, it is recommended to conduct chemical and rheological analysis for further characterization of the durian seed flour and its effect in the cookies for further studies.